2009
DOI: 10.1111/j.1469-8749.2008.03195.x
|View full text |Cite
|
Sign up to set email alerts
|

Are infants with torticollis at risk of a delay in early motor milestones compared with a control group of healthy infants?

Abstract: Recently it has been claimed that infants with congenital muscular torticollis (CMT) are at risk of a delay in early motor milestones. The aim of the present study was to investigate whether infants with CMT are indeed at risk in comparison with a control group of healthy infants. A second aim was to investigate whether the time spent in a prone position and plagiocephaly had any influence on motor development. Eighty‐two infants with CMT (35 females and 47 males) were compared with 40 healthy infants (18 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 24 publications
0
55
3
3
Order By: Relevance
“…1,9,10 In an earlier study, a prospective follow-up study of 83 infants with congenital torticollis assessed at 2.9 and 12.8 months of age, Schertz et al 9 had found early motor developmental delay in the majority of infants with torticollis at 2.9 months but only in a minority of them at 12.8 months; all were assessed with the Alberta Infant Motor Scale. In a similar study by Ohman et al, 10 a group of children with congenital torticollis, all treated at a department of physiotherapy in a hospital in Sweden, scored significantly lower in motor development assessment at 2 and 6 months of age in comparison to the control group, but there were no differences between the groups at 18 months. Here, motor development was also assessed with the Alberta Infant Motor Scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,9,10 In an earlier study, a prospective follow-up study of 83 infants with congenital torticollis assessed at 2.9 and 12.8 months of age, Schertz et al 9 had found early motor developmental delay in the majority of infants with torticollis at 2.9 months but only in a minority of them at 12.8 months; all were assessed with the Alberta Infant Motor Scale. In a similar study by Ohman et al, 10 a group of children with congenital torticollis, all treated at a department of physiotherapy in a hospital in Sweden, scored significantly lower in motor development assessment at 2 and 6 months of age in comparison to the control group, but there were no differences between the groups at 18 months. Here, motor development was also assessed with the Alberta Infant Motor Scale.…”
Section: Discussionmentioning
confidence: 99%
“…13 Most likely, infants with torticollis are not able to do this because of the fixation of the head in lateral flexion and contralateral rotation, which would disturb sensory information about positional symmetry and balance as well as the weight-shifting movements necessary for transitioning from one posture to another. Ohman et al 10 found that infants who spend more time in the prone position when awake show earlier development of gross motor skills compared with infants who spend no or little time in this position. Furthermore, she found that the group with congenital torticollis spent less time in the prone position compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ireland et al (23) examined the developmental milestones in children with achondroplasia and found a delay in the ages of acquisition of gross motor skills. Ohmann et al (24) compared the ages of acquisition of gross motor skills of infants with congenital muscular torticollis with the ages of an healthy group in 2009. They found a significant retardation in the ages of acquisition of motor function in the early period in the infants with muscular torticollis compared to the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…Baş tilti; omuz, göğüs kafesi, abdominal kaslara etkiyerek postür kontrolü ve hareket gelişiminde, duyu-motor koordinasyon üzerine olumsuz etkiyle kaba motor fonksiyonda geriliğe sebep olmaktadır (14). Bu çocuklarda aynı zamanda üst ekstremite kullanımında asimetri, normalin altı kognitif fonksiyon, postür ve denge kontrolünde etkilenme saptanabilir (14,20,21). Dolayısıyla bu bebeklerde erken dönemde fizik tedavi ve rehabilitasyon başlanmalıdır (20).…”
Section: Etiyopatogenezunclassified